Description of different developmental stages of centrocestus formosanus (nishigori, 1924) (Digenea: Heterophyidae) - Hernández, Luz Elena; Díaz, Marcos; Bashirullah, Abul (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Descriptions of the different imrnature stages (redia, cercaria, and metacercaria) and adult stage of Centrocestus formosanus (Nishigori) are presented. Between 32 and 36 circumoral spines are generally reported for the C. fonnosanus, and in this study 32 circumoral spines were found on the C. formosanus collected in Sucre state, Venezuela. Experimental infection on different types of hosts show a high susceptibility of infection for the C. formosanus rnetacercariae.